2020
DOI: 10.1007/s00415-020-10197-8
|View full text |Cite
|
Sign up to set email alerts
|

Why do SARS-CoV-2 NSPs rush to the ER?

Abstract: SARS-CoV-2, which led to the 2020 global pandemic, is responsible for the Coronavirus Disease 2019 (COVID-19), a respiratory illness, and presents a tropism for the central nervous system. Like most members of this family, the virus is composed of structural and non-structural proteins (NSPs). The non-structural proteins are critical elements of the replication and transcription complex (RTC), as well as immune system evasion. Through hijacking the endoplasmic reticulum (ER) membrane, NSPs help the virus estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 105 publications
1
74
0
14
Order By: Relevance
“…Coronaviruses, including SARS-CoV-2 that replicate in the cytoplasm compartmentalize their genome transcription in organelle-like structures thereby protecting the virus against host cell defenses and increasing the replication efficiency (Santerre et al 2020). We previously mapped the structural proteins of SARS-CoV-2 and demonstrated that the M protein the virus resembles the sugar transporter SemiSWEET (Thomas, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronaviruses, including SARS-CoV-2 that replicate in the cytoplasm compartmentalize their genome transcription in organelle-like structures thereby protecting the virus against host cell defenses and increasing the replication efficiency (Santerre et al 2020). We previously mapped the structural proteins of SARS-CoV-2 and demonstrated that the M protein the virus resembles the sugar transporter SemiSWEET (Thomas, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The nsps are critical elements of the replication and transcription complex (RTC), as well as immune system evasion. Through hijacking the endoplasmic reticulum (ER) membrane, nsps help the virus establish the RTC (Santerre et al 2020). The structure and function of nsps of SARS-CoV-2 is similar to SARS-CoV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nsp3 (217 kDa; 1946 amino acids) produced by both pp1a and pp1ab, is the largest element of the replication and transcription complex (RTC) [ 35 ]. It contains multiple conserved domains that represent an N-terminal acidic phosphoesterase, a papain like protease (PLpro), Y-domain, transmembrane domain 1 (TM1) and an adenosine diphosphate-ribose 1′’-phosphatase (ADRP) (NCBI reference sequence YP_009725299) [ 2 ].…”
Section: The Non-structural Proteins Encoded By the Sars-cov-2 Genmentioning
confidence: 99%
“…The remaining three restriction sites are cleaved by viral papain-like protease (PLpro, NSP3), which is also involved in the evasion of host antiviral immune responses [ 21 , 24 ]. Replication is initiated by the assembly of a replication/transcription complex (RTC), which concentrates the necessary NSPs in a microenvironment close to the viral RNA [ 25 ]. The central component of the RTC, formed by viral RNA-dependent RNA-polymerase (RdRp, NSP12) and its cofactors NSP7 and NSP8, has the capacity to generate full-length negative-strand RNA chains that serve as templates for the synthesis of positive-strand genomic (gRNA) and subgenomic (sgRNA) RNA [ 21 , 26 ] ( Figure 2 ).…”
Section: Sars-cov-2 Structure Infection Replication and Treatmenmentioning
confidence: 99%